Failure in the adhesion of hydroxyapatite coatings to surgical screws: a fourier transform infrared spectroscopy qualitative study - Pereyra, Mariana; Navatta, Marco; Méndez, Eduardo (Frontiers in Coatings, Dyes and Interface Engineering, 2025)
Failure in the adhesion between hydroxyapatite and the metallic substrate in commercial biomaterials is one of the significant drawbacks in implantology. The demand for confident analytical methods to characterize these coatings is met through a rigorous research process. Fourier-transform infrared spectroscopy (FTIR) was chosen as the method to characterize hydroxyapatites. A meticulous data analysis from FTIR spectra was conducted, and an FTIR library was constructed from FTIR spectra of different types of hydroxyapatites, considering several chemical environments. The analytical procedure involved the registry of the spectra, localization of the leading absorption bands from the minima of the second derivative spectra, and reconstitution of the original spectra by curve deconvolution. The FTIR library was employed to analyze commercial surgical screws that failed in their use in different implants. Our methodology identified the structural reasons for such failure, caused by the selective removal of non-apatitic environments during adsorption onto the metallic implant. The method identifies the adhesion degree of the apatite coating on the implant before implantation in a biological organism, thereby preventing additional patient interventions and the associated costs.